Analysis of adhesive domains from the A4VAR Plasmodium falciparum erythrocyte membrane protein-1 identifies a CD36 binding domain. - Smith, J; Kyes, S; Craig, A; Fagan, T; Hudson-Taylor, D; Miller, L; Baruch, D; Newbold, C (1998)
The A4VAR is a variant antigen expressed by a clonal line that binds CD36 and intercellular adhesion molecule-1, ICAM-1. We have cloned and sequenced the extracellular domain coded by the A4var gene. To probe the relationship between A4var expression and parasite adhesion to ICAM-1, var mRNA and protein expression were analyzed in an enriched population of A4 parasites that displayed higher ICAM-1 binding. By Northern analyses, A4var was the predominant var message and antisera raised against a recombinant A4VAR protein reacted with the majority of infected erythrocytes, reinforcing previous conclusions that A4VAR binds ICAM-1. A4VAR contains five Duffy-binding like (DBL) domains, and two cysteine-rich interdomain regions (CIDR) domains. DBL and CIDR domains from A4VAR were expressed in mammalian cells to determine which regions mediate binding to CD36 and ICAM-1. Using several different binding assays, the A4VAR CIDR1 was the only domain found to bind CD36. In contrast, the same assays were unable to identify the ICAM-1 binding domain in A4VAR. This is the first time that each of the DBL and CIDR domains from a Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) have been systematically expressed and tested for binding. These results confirm that CIDR1 is sufficient to bind CD36 without any apparent contribution from other domains.